Impact of the PPOS protocol on euploidy embryo rates and reproductive outcomes in preimplantation genetic testing cycles: a systematic review - Mei, Youwen; Wang, Yacong; Kuang, Li; Lin, Yonghong; Wang, Fang (Frontiers in Endocrinology, 2025)
The success of assisted reproductive technology (ART) relies on the quality of embryos, particularly the euploid status, which is influenced by controlled ovarian hyperstimulation (COH) protocols. In recent years, the progesterone-primed ovarian stimulation (PPOS) protocol has gained popularity due to its potential benefits. However, the impact of PPOS on euploid embryo rates (EER) and reproductive outcomes remains incompletely understood. Therefore, we conducted this review to comprehensively assess this impact by comparing the PPOS with conventional COH protocols in PGT cycles. The results revealed that the PPOS protocol demonstrated comparable EER and reproductive outcomes to conventional COH protocols in the general population. Among patients with a good prognosis, EER and associated reproductive outcomes with PPOS may be less favorable. However, in individuals with a poor prognosis, PPOS showed comparable or even superior outcomes. Additionally, the timing of cycle initiation, whether in the follicular or luteal phase, had no significant impact on clinical outcomes in patients with diverse ovarian responses.